Le Gal, Jean (2005). Los derechos del niño en la escuela. Una educación para la ciudadanía. Barcelona: Graó. - Claudia Messina Albarenque (Universidad Autónoma de Madrid, 2018)
The author, a French professor, member of the Freinet Movement emerged towards the end of the 20s of the 20th century and the League of Human Rights, links two issues of enormous relevance and relevance: the rights of the child in school and education for the citizenship.